Parameters of radionuclide washout from the catchment area of the Viliya river after the accident at the Belarusian NPP - Zhukova, Olga M.; Kliaus, Victoria V.; Nikolaenko, Elena V. (Journal of the Belarusian State University. Ecology, 2020)
This article presents the results of calculation the parameters of radionuclides washout from the catchment areas of the Viliya river and the assessment of activity concentrations of radionuclides in water in case of beyond design basis accident at the Belarusian NPP. The results of estimates of the exposure doses to public living near the Belarusian NPP from the consumption of drinking water contaminated with 137Cs, 90Sr and 131I radionuclides as a result of a possible beyond design basis accident are presented.
Keywords: radionuclide; water; Belarusian NPP; beyond design basis accident; Viliya; washout module; washout coefficient; effective dose